Patients' Perception Towards Quality of Nursing Care and Associated Factors at Agaro General Hospital, Southwest Ethiopia: A Cross-Sectional Study - Mohammed Yesuf MSc; Mehd Abdu MSc (SAGE Publishing, 2023)
Introduction Quality care is currently on the agenda of policy-makers at national and international levels. Patient-centeredness is considered an integral component of healthcare quality dimensions in addition to its effectiveness and safety. This indicates that healthcare should be viewed from a patient's perspective. Methods and Materials An institution-based cross-sectional study was conducted with a total sample size of 422 using systematic random sampling among patients admitted to the Agaro General Hospital. SPSS software version 25.0 was used to enter and analyze the data. The relationship between the dependent variable and covariates was determined using multivariable binary logistic regression analysis. Results A total of 405 patients participated in this study with a response rate of 96.0%. The overall percentage of positive perception was 76.3%. Clients aged 31-40 years were more likely [AOR: 2.191, 95% CI: 1.033-4.645, p -value: .041] and clients aged ≥ 51 years were less likely to perceive positively [AOR: 0.490, 95% CI: 0.271-0.886, p -value: .018]. Patients who had paid for receiving care were more likely to perceive it positively [AOR: 3.046, 95% CI 1.043-8.896, p -value: .042]. The odds of positive perception towards the quality of nursing care were higher among patients who thought the hospital cost was medium [AOR: 3.066, 95% CI: 1.286-7.311, p -value: .012], low [AOR: 13.859, 95% CI: 2.245-85.562, p -value: .005], and uncertain [AOR: 6.116, 95% CI: 1.988-18.809, p -value: .002]. Conclusion and Recommendations Most patients had a positive perception of the quality of nursing care. Being elderly and feeling towards hospital costs have a negative influence whereas having paid for the treatment has a positive influence on the patients' perception of nursing care. Hence the need increases with age, and healthcare providers should pay great attention while providing care for elderly patients.